Assessing influence in biofuel production and ecosystem services when environmental changes affect plant–pest relationships. Issue 10 (1st August 2020) - De Simone, Walter; Iannella, Mattia; D'Alessandro, Paola; Biondi, Maurizio
Abstract: Climate change is currently affecting both biodiversity and human activities; land use change and greenhouse gas emissions are the main drivers. Many agricultural services are affected by the change, which in turn reflects on the basic provisioning services, which supply food, fibre and biofuels. Biofuels are getting increasing interest because of their sustainability potential. Jatropha curcas gained popularity as a biodiesel crop, due to its ease of cultivation even in harsh environmental conditions. Notwithstanding its high economic importance, few studies are available about its co‐occurrence with pests of the genus Aphthona in sub‐Saharan Africa, where these insects feed on J. curcas, leading to relevant economic losses. Using ecological niche modelling and GIS post‐modelling analyses, we infer the current and future suitable territories for both these taxa, delineating areas where J. curcas cultivations may occur without suffering the presence of Aphthona, in the context of future climate and land use changing. We introduce an area‐normalized index, the 'Potential‐Actual Cultivation Index', to better depict the ratio between the suitable areas shared both by the crop and its pest, and the number of actual cultivations, in a target country. Moreover, we find high economic losses ( −50%) both in terms of carbon sequestration and in biodiesel production when J. curcas co‐occur with the Aphthona cookei species group. Abstract : Jatropha curcas (Euphorbiaceae) gained popularity in biofuel production, thanks to the ease of cultivation in different environments. In sub‐Saharan Africa, the Aphthona cookei species group (Coleoptera, Chrysomelidae), which feed on this plant, cause relevant economic losses. Our study addresses the co‐occurrence of J. curcas with this pest. We coupled ecological niche modelling and GIS analyses to predict the current and future suitable territories for both the taxa and identify areas where J. curcas may be grown without suffering the presence of Aphthona, considering climate and land use change. High economic losses ( −50%) resulted when J. curcas co‐occurs with Aphthona .